Insetos necrófagos: marcas em remanescentes arqueológicos ósseos humanos - Seixas, Caroline de Santana (2019)
This work proposes an inventory and reflect on previous studies about the process of decomposition of the body and marks left by insects scavengers in human bone remains and how they contribute to the formation process in the biocultural contexts. Thus, we seek a greater interaction between forensic and forensic disciplines with Archeology, facilitating the application of methods and techniques, considering the possible diagnoses with the presence of insects in an archaeological context.